2012
DOI: 10.1038/bjc.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of everolimus with biomarker exploration in patients with advanced gastric cancer refractory to chemotherapy including fluoropyrimidine and platinum

Abstract: Background:To evaluate the activity and safety of everolimus and identify potential biomarkers for efficacy of everolimus in patients with advanced gastric cancer (AGC), who failed both fluoropyrimidine and platinum.Methods:Fifty-four patients received everolimus (10 mg day−1). The primary objective was to determine the 4-month progression-free survival (PFS) rate, assumed to be 30%. We additionally investigated the potential biomarkers for everolimus as an exploratory endpoint in those who underwent tumour bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 15 publications
0
50
1
3
Order By: Relevance
“…Twenty trials reported pneumonitis events, eight trials reported cough, and twelve trials reported dyspnea. Sixteen trials (seven temsirolimus, eight everolimus, and one ridaforolimus) were single arm studies or randomized patients to different doses/schedules of an mTOR inhibitor (Table 2) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Six trials (one temsirolimus, four everolimus, and one ridaforolimus) randomized patients to an mTOR inhibitor arm or a non-mTOR inhibitor control arm (Table 3) [22-27].…”
Section: Search Resultsmentioning
confidence: 99%
“…Twenty trials reported pneumonitis events, eight trials reported cough, and twelve trials reported dyspnea. Sixteen trials (seven temsirolimus, eight everolimus, and one ridaforolimus) were single arm studies or randomized patients to different doses/schedules of an mTOR inhibitor (Table 2) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Six trials (one temsirolimus, four everolimus, and one ridaforolimus) randomized patients to an mTOR inhibitor arm or a non-mTOR inhibitor control arm (Table 3) [22-27].…”
Section: Search Resultsmentioning
confidence: 99%
“…As an increasing number of targeted agents have been used in recent clinical trials [41], ramucirumab, a new monoclonal antibody VEGFR-2 antagonist, has shown survival benefits after first-line chemotherapy [42]. Further active investigations with target agents are needed based on biomarkerdriven clinical trials [34].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapies such as trastuzumab [10], cetuximab [29,30], sorafenib [31], bevacizumab [32], vorinostat [33] and everolimus [34] were administered to a total of 262 patients (6.7 %) as first-line treatment, and these were also the most commonly used in period 3. Use of oral fluoropyrimidine increased significantly since period 2 (p for trend \0.001) [15-18, 22, 23, 35].…”
Section: Betweenmentioning
confidence: 99%
“…It prevents mTOR from phosphorylating S6K1 and 4EBP1, halting protein synthesis and blocking cell cycle progression [112,115]. Higher expression of S6 proteins was associated with a higher disease control rate and longer PFS in a phase II second-line study of everolimus in GC [118]. The phase III Gastric Anti-Tumor Trial with Everolimus (GRANITE-1) study compared everolimus plus best supportive care with placebo plus best supportive care in patients with advanced GC who had progressed after one or two lines of chemotherapy [119].…”
Section: Mammalian Target Of Rapamycinmentioning
confidence: 99%